Innovative approach for improved sustained delivery of metformin hydrochloride for its anti-hyperglycemic activity - Pillai, M Kar; Pillai, S; Jain, S (Creative Pharma Assent, 2024)
Metformin hydrochloride, an antidiabetic agent, is useful in reducing the blood glucose concentration in Type II diabetes. It is also finding its use as a repurposed drug. The formulations consisted of micro drug delivery systems prepared by emulsification method and were evaluated in-vitro and in-vivo. Process variables like amount of polymer, speed of agitation and stirring, presence or absence of surfactant and cross linker offered a versatile approach towards obtaining the formulation though affected physicochemical properties of formulations. Discrete, spherical, and free-flowing microspheres, in the size range and granularity of 250 to 700µ were used to control the drug release rate. Drug release was diffusion controlled as evident from the Higuchi kinetics. The physical characteristics of the formulations were reproducible. Healthy and alloxan induced hyperglycaemic male albino mice were used for in-vivo experimentation by evaluating plasma glucose level reduction and % reduction in the blood glucose level after administration of pure drug and formulations. The results indicate significant sustained fall in the blood glucose level for about 10 hrs following formulation administration as compared to the pure drug.